Tourism marketing in the age of the consumer - Morrison, Alastair M. (New York Routledge, Taylor & Francis Group, 2022)
"Tourism Marketing: In the Age of the Consumer offers a fresh and contemporary approach as an introductory textbook on tourism marketing. Six major themes along with the traditional core marketing principles are blended together
Part 1. THE CONSUMER -- Part 2. THE STRATEGY -- Part 3. THE IMPLEMENTATION -- Part 4. THE TOURISM PRODUCT -- Part 5. THE EVALUATION OF TOURISM MARKETING.
Includes bibliographical references and index.
Keywords: Hospitality industry -- Marketing; Service industries -- Marketing; Tourism -- Computer network resources; Tourism -- Marketing